Botulinum toxin (Dysport®) treatment of hip adductor spasticity in multiple sclerosis: a prospective, randomised, double blind, placebo controlled, dose ranging study. Issue 6 (1st June 2000) - Hyman, N; Barnes, M; Bhakta, B; Cozens, A; Bakheit, M; Kreczy-Kleedorfer, B; Poewe, W; Wissel, J; Bain, P; Glickman, S; Sayer, A; Richardson, A; et al.
Abstract : OBJECTIVE: To define a safe and effective dose of Dysport for treating hip adductor spasticity. METHODS: Patients with definite or probable multiple sclerosis, and disabling spasticity affecting the hip adductor muscles of both legs, were randomised to one of four treatment groups. Dysport (500, 1000, or 1500 Units), or placebo was administered by intramuscular injection to these muscles. Patients were assessed at entry, and 2, 4 (primary analysis time-point), 8, and 12 weeks post-treatment. RESULTS: A total of 74 patients were recruited. Treatment groups were generally well matched at entry. The primary efficacy variables—passive hip abduction and distance between the knees—improved for all groups. The improvement in distance between the knees for the 1500 Unit group was significantly greater than placebo (p=0.02). Spasm frequency was reduced in all groups, but muscle tone was reduced in the Dysport groups only. Pain was reduced in all groups, but improvements in hygiene scores were evident only in the 1000 Unit and 1500 Unit groups. Duration of benefit was significantly longer than placebo for all Dysport groups (p<0.05). Adverse events were reported by 32/58 (55%) Dysport patients, and by 10/16 (63%) placebo patients. Compared with the two lower dose groups, twice as many adverse events were reported by the 1500 Unit group (2.7/patient). The incidence of muscle weakness was higher for the 1500 Unit group (36%) than for placebo (6%). The response to treatment was considered positive by two thirds of the patients in the 500 Unit group, and by about half the patients in the other groups. CONCLUSION: Dysport reduced the degree of hip adductor spasticity associated with multiple sclerosis, and this benefit was evident despite the concomitant use of oral antispasticity medication and analgesics. Although evidence for a dose response effect was not statistically significant, there was a clear trend towards greater efficacy and duration of effect with higher doses of Dysport. Dysport treatment was well tolerated, with no major side effects seen at doses up to 1500 Units. The optimal dose for hip adductor spasticity seems to be 500–1000 Units, divided between both legs.